Outcome of radiological interventions in pediatric gastrointestinal diseases: A large tertiary center experience. Issue 2 (27th December 2018) - Nabi, Zaheer; Singh, Jagadeesh R; Haris, Arafat; Shava, Upender; Chavan, Radhika; Nageshwar Reddy, Duvvur
Abstract : Background: Interventional radiology (IR) is an indispensable component of multidisciplinary care in various gastrointestinal (GI) diseases. The literature on safety and utility of IR is limited in children. Objectives: In this study, we aim to analyze the outcomes of IR in various pediatric GI diseases. Methods: The data of children (≤18 years) who underwent radiological interventions for GI disorders (2009–2017) were analyzed, retrospectively. The indications for interventions included vascular (Budd Chiari syndrome [BCS], pseudoaneurysm) and nonvascular (pancreatic fluid collections [PFCs], cholangitis and anastomotic biliary strictures). The outcomes of radiological interventions, including success and adverse events, were assessed. Results: A total of 93 children (mean age 13.45 ± 4.09 years) underwent radiological interventions for vascular (chronic BCS = 14, pseudoaneurysm = 28) or nonvascular (PFCs = 33, hepaticojejunostomy strictures or leaks = 12, cholangitis = 6) indications. Of 33 children who underwent drainage of PFCs, clinical success was noticed in 32 children during a mean follow‐up of 32.4 ± 21.66 months; 11 children with persistent external pancreatic fistula were managed with endoscopic pancreatic ductal stenting (8 children) and internalization of transgastric drain (3 children). In children who underwent hepatic vein or inferior vena cava stenting for BCS, mean stent patency was 78.57% during a follow‐up of 24.1 ± 13.78 months. In children with pseudoaneurysms, angioembolization was successfully performed in 92.8% patients. Re‐bleeding was noticed in two children, one of whom required reintervention. In children who underwent percutaneous transhepatic biliary drainage, resolution of anastomotic strictures was noticed in all during a follow‐up of 36.1 ± 13.73 months. Conclusion: Interventional radiology is safe and effective in the management of various pediatric GI diseases. Abstract : Interventional radiology is indispensable for multidisciplinary care of pediatric gastrointestinal (GI) diseases. In this study, we present the outcomes of radiological interventions in a wide spectrum of GI disorders in the pediatric population.